2018
DOI: 10.3390/ijms19030691
|View full text |Cite
|
Sign up to set email alerts
|

Minoxidil Promotes Hair Growth through Stimulation of Growth Factor Release from Adipose-Derived Stem Cells

Abstract: Minoxidil directly promotes hair growth via the stimulation of dermal papilla (DP) and epithelial cells. Alternatively, there is little evidence for indirect promotion of hair growth via stimulation of adipose-derived stem cells (ASCs). We investigated whether minoxidil stimulates ASCs and if increased growth factor secretion by ASCs facilitates minoxidil-induced hair growth. Telogen-to-anagen induction was examined in mice. Cultured DP cells and vibrissae hair follicle organ cultures were used to further exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 37 publications
0
57
0
1
Order By: Relevance
“…THPO may be an important place for megakaryocytopoiesis in blood vessels [24]. Interestingly, vasodilators such as minoxidil and udenfil stimulated ASC motility, thereby inducing hair growth [25,26]. The relationship between the THPO level, vasodilation, and hair growth should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…THPO may be an important place for megakaryocytopoiesis in blood vessels [24]. Interestingly, vasodilators such as minoxidil and udenfil stimulated ASC motility, thereby inducing hair growth [25,26]. The relationship between the THPO level, vasodilation, and hair growth should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Initially developed for the treatment of male-and femalepattern baldness, minoxidil is now widely used off-label for the treatment of many types of hair loss including AA. It exerts its effects by inducing growth factors from DP cells (vascular endothelial growth factor, hepatocyte growth factor, and IGF-1); activating the DP b-catenin pathway; increasing blood flow by dilating HF arteries, resulting in induction and prolongation of anagen (Otomo, 2002); and stimulating the telogen-to-anagen induction (Choi et al, 2018) (Figure 1c and d). Several placebo-controlled studies have shown minoxidil to stimulate hair growth in patients with AA when applied daily (El Taieb et al, 2016;Price, 1987), although cosmetically acceptable results were not often obtained with minoxidil as a monotherapy.…”
Section: Minoxidilmentioning
confidence: 99%
“…Minoxidil (MXD) is the most widely used drug in alopecia treatment, especially male-pattern hair loss [1][2][3][4][5][6][7]. It is known to have a vasodilatory effect and expedite secretion of growth factors for hair regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the characteristics of alopecia, it works effectively when applied to the topical skin area through transdermal delivery of MXD. However, typical MXD delivery has the disadvantages of low efficiency of transdermal delivery and various side effects, such as tolerance, inflammation and low blood pressure [6]. Therefore, many studies have been investigated to improve the transdermal delivery efficiency of MXD applied to the skin and the therapeutic efficacy in alopecia, through the transdermal routes such as hair follicles, sweat glands or microneedle arrays [2,4,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%